2019
DOI: 10.1029/2018jb017131
|View full text |Cite
|
Sign up to set email alerts
|

Shear Velocity Structure Beneath Saudi Arabia From the Joint Inversion of P and S Wave Receiver Functions, and Rayleigh Wave Group Velocity Dispersion Data

Abstract: We develop a new 3-D shear velocity model for the lithosphere and sublithospheric mantle under Saudi Arabia by jointly inverting P wave receiver functions, S wave receiver functions, and fundamental-mode Rayleigh wave group velocities. P and S receiver functions are calculated from earthquakes recorded between 2012 and 2015 at 156 Saudi National Seismic Network stations operated by the Saudi Geological Survey. Rayleigh wave dispersion data are extracted from independent tomographic studies. Our model reveals s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 65 publications
5
20
0
Order By: Relevance
“…The sedimentary cover in the Arabian Platform gradually thickens eastward and reaches more than 10 km thickness beneath the Mesopotamian Foredeep and Persian Gulf (Seber 1997). Figures 4, 9 and S11) suggest that on average the Arabian Shield has higher crustal seismic velocities than the Arabian Platform, in agreement with previous studies (Hansen et al, 2007(Hansen et al, , 2008Tang et al, 2016Tang et al, , 2018Tang et al, , 2019. The velocity map at 8-km depth (Figure 4) exhibits high velocities beneath the Arabian Shield and Afar depression where magmatic crystalline rocks are exposed at shallow depths.…”
Section: Arabian Plate the Red Sea And Afar Depressionsupporting
confidence: 89%
See 4 more Smart Citations
“…The sedimentary cover in the Arabian Platform gradually thickens eastward and reaches more than 10 km thickness beneath the Mesopotamian Foredeep and Persian Gulf (Seber 1997). Figures 4, 9 and S11) suggest that on average the Arabian Shield has higher crustal seismic velocities than the Arabian Platform, in agreement with previous studies (Hansen et al, 2007(Hansen et al, , 2008Tang et al, 2016Tang et al, , 2018Tang et al, , 2019. The velocity map at 8-km depth (Figure 4) exhibits high velocities beneath the Arabian Shield and Afar depression where magmatic crystalline rocks are exposed at shallow depths.…”
Section: Arabian Plate the Red Sea And Afar Depressionsupporting
confidence: 89%
“…In regions where continuous seismic noise records were not available, such as Saudi Arabia, we incorporated dispersion curve data from previous studies to improve ray coverage. We used the dispersion measurements by Tang et al (2018Tang et al ( , 2019 for Rayleigh waves (periods 8-75s) observed at 143 permanent broadband stations of the Saudi National Seismic Network (SNSN) (green triangles in Figure 2) for regional earthquakes (EQ) located inside our study area. The inclusion of these EQ-based dispersion data dramatically improves the ray coverage across Arabia ( Figure S3).…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations